Multiplicity in parameter‐dependent problems for ordinary differential equations - Sadyrbaev, Felix (Mathematical Modelling and Analysis, 2009)
We consider two types of nonlinear boundary value problems involving parameters. The second type of problems includes the Fučík problem. Properties of spectra are discussed in connection with the number of solutions to BVP. First published online: 14 Oct 2010